THE RELATIONSHIP BETWEEN EDUCATION AND KNOWLEDGE ABOUT DIABETES MELLITUS IN THE COASTAL AREA OF LAPULU DISTRICT: DIABETES MELLITUS - Indra, Indra; Rahmadania, Wa Ode; Novianti, Asri Dwi; Nawawi, Nawawi; Ardiansyah, La Ode; Abd. Azis, Moh. Nisyar Sy.; Firmansyah, Firmansyah (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2024)
Background: Diabetes mellitus (DM) is a condition of chronic hyperglycemia that is often accompanied by various metabolic disorders due to hormonal disorders, which can cause various chronic complications. Based on data from the Kendari City Health Service in 2020, in Kendari City there were 3,030 people suffering from DM and in Lapulu Village, one of the cases was that many people suffered from diabetes mellitus. The aim of this research was to determine Relationship Between Education With Knowledge About Diabetes Mellitus In The Coastal Area Of Lapulu District. Methods: This type of research is quantitative research with a Cross Sectional analysis design. The research population is the people of Lapulu Village, Kendari City. The number of samples in this study was 43 people using a purposive sampling technique. The analysis method used is fisher’s exact test. Results: The results of this study obtained a significant value of p = 0.000 or less than 0.05. Conclusion: There is a relationship between education and knowledge about diabetes mellitus in the Coastal Area of Lapulu Village. Suggestions for community health centers of Abeli to carry out routine activity programs to increase public knowledge about Diabetes Mellitus, namely by conducting routine health education or counseling every month.